The Use of Ketamine as an Antidepressant: A Narrative Literature Review - Lovina Lovina (HM Publisher, 2021)
Ketamine is a structural analog of the dissociative anesthetic and recreational drug phencyclidine (PCP). Like phencyclidine, ketamine causes analgesia and amnesia without the cardiovascular and respiratory depression associated with general anesthesia. This review aimed to describe the use of ketamine as an antidepressant. Ketamine reverses CSP in the prefrontal cortex, hippocampus, and NAc within one day of administration via postsynaptic glutamate activation with upregulation of neurotrophic signaling and increased protein synthesis, restoring synaptic connectivity lasting for days or even weeks. The antidepressant properties of ketamine may also be due to its effect on mitochondrial energy metabolism. Ketamine as an anesthetic has been developed in clinical practice because other significant effects have been found, namely as an antidepressant. In conclusion, monitoring must be carried out in antidepressant therapy administration because ketamine has possible side effects such as hypersalivation, tachycardia, increased systemic arterial pressure, and intracranial pressure.